The Principle of Proportionality in Drug Offenses and Its Effective Factors in the Application of Iranian and Western Laws - Elham Heidari (پژوهش تطبیقی حقوق اسلام و غرب, 2023)
The principle of proportionality in criminal law is considered one of the fundamental principles, which entails determining punishments that correspond to the social harm caused by the crime. In the case of drug offenses, the application of this principle during the legislative stage requires careful consideration and subtlety on the part of the Legislature due to the complexity of such offenses. By taking into account the effective factors in the application of the principle of proportionality, unjustness in the determination and implementation of punishments can be minimized, and the expected goals of punishment, such as deterrence, can be better achieved. The behavior of the offender, the nature of the committed crime, the role of the accused, their involvement in the crime, and the severity and gravity of the offense are among the most influential factors in the application of the principle of proportionality in drug offenses. However, the Legislature in the Anti-Drug Law has solely emphasized the proportionality between the quantity of drugs and the level of punishment, disregarding other essential factors.